EVALUASI POTENSI INTEGRASI PROGRAM KAWASAN STRATEGIS NASIONAL BOROBUDUR DENGAN PROGRAM PEMBANGUNAN DESA DI KAWASAN BOROBUDUR - , RAISYA NUR NASICH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aim of the research is to evaluate the potential integrating Kawasan Strategis Nasional Borobudur program with village development program in Borobudur. This can be operationalized into three detailed objective: 1) describe the national strategic area Borobudur program and the villages development program in the region Borobudur, 2) evaluate the potential integrating national strategic area Borobudur program with village development program in the region Borobudur, 3) Identify factors suspected to be affected the program implementation national strategic area Borobudur based on village development program. The theory that would be used to this research is program development, integration and factors which influence policy implementation. Research method that is used to achieve the aim of the research is deductive qualitative. The theory was sent into the variable and indicators to be used as a guidance for data collection, interview and observation field. This research found a potential integrating among the national strategic area Borobudur program and the village development program in the region Borobudur. It was based from advantages and disadvantage of the two programs. The national strategic area Borobudur program aims to preserve the heritage in the area, but less attention to the needs of people because less participation during the preparation process. The implementation national strategic area Borobudur in to supported by state budget, revised local government budget and local government budget. In the other side, the village development program had an solve problems existing in the village because involve the participation of people during the preparation process. The national strategic area Borobudur implementation had two factors that to be affected is communication and adjustment program.